Parasympathetic innervation maintains epithelial progenitor cells during salivary organogenesis - Knox, S.M. (2010)
The maintenance of a progenitor cell population as a reservoir of undifferentiated cells is required for organ development and regeneration. However, the mechanisms by which epithelial progenitor cells are maintained during organogenesis are poorly understood. We report that removal of the parasympathetic ganglion in mouse explant organ culture decreased the number and morphogenesis of keratin 5-positive epithelial progenitor cells. These effects were rescued with an acetylcholine analog. We demonstrate that acetylcholine signaling, via the muscarinic M1 receptor and EGFR, increased epithelial morphogenesis and proliferation of the keratin 5-positive progenitor cells. Parasympathetic innervation maintained the epithelial progenitor cell population in an undifferentiated state, which was required for organogenesis. This mechanism for epithelial progenitor cell maintenance may be targeted for organ repair or regeneration.